2013
DOI: 10.1016/j.ophtha.2013.07.055
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Functional Vision Questionnaire for Children and Young People with Visual Impairment

Abstract: We have developed a novel, psychometrically robust self-report questionnaire for children and young people-the FVQ_CYP-that captures the functional impact of visual disability from their perspective. The 36-item, 4-point unidimensional scale has potential as a complementary adjunct to objective clinical assessments in routine pediatric ophthalmology practice and in research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 17 publications
(24 reference statements)
2
93
0
Order By: Relevance
“…12 Each family received a study pack containing an invitation letter, information sheets for children and parents, consent and assent forms, large print and electronic (CD) versions of the child and parental instrument versions, described below, and a prepaid postage reply envelope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Each family received a study pack containing an invitation letter, information sheets for children and parents, consent and assent forms, large print and electronic (CD) versions of the child and parental instrument versions, described below, and a prepaid postage reply envelope.…”
Section: Methodsmentioning
confidence: 99%
“…One assesses vision-related quality of life (VQoL) 11 and the other functional vision (FV), 12 each uniquely capturing the impact of living with VI in children.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Impact of Vision Impairment for Children (IVI-C) instrument 13 can be used to assess the impact of visual impairment on VR-QoL, and the Cardiff Visual Ability Questionnaire for Children (CVAQC) 14 and the Functional vision questionnaire for children and young people with visual impairment 15 , to assess the impact on activities of daily living (functional visual ability).…”
mentioning
confidence: 99%
“…Interestingly, the CVAQC-CN showed better psychometric properties compared with the original and Turkish versions. In addition, the CVAQC-CN had better Rasch-based psychometric properties in terms of discrimination ability, fit statistics and dimensionality than the other existing instruments 2 10 12 14. Moreover, the TIC of the CVAQC-CN showed that the instrument provides visual ability scores with a high-level accuracy over the entire range of measures, irrespective of respondent's level of visual disability (figure 2).…”
Section: Discussionmentioning
confidence: 98%
“…There are a few validated instruments in this targeted demographics; although developed in other countries, they demonstrated promising content coverage and psychometric properties 2 9–12 14. We chose the CVAQC for this study because it has a content that primarily focuses on school activities, and possesses excellent psychometric properties 7.…”
Section: Discussionmentioning
confidence: 99%